Varieties of Affect - Armon-Jones, Claire (Book collections on Project MUSE., 1991)
In this new and original book, Claire Armon-Jones examines the concept of affect and various philosophical positions which attempt to define and characterize it: the standard view, the neo-cognitivist view, and the objectual thesis. She contends that these views radically distort our understanding of affect by disregarding modes of affect which fail to conform to the accounts they each employ. Against the standard and neo-cognitivist views she argues that the notions they use to characterize affect are neither necessary nor sufficient; and against the objectual thesis she further argues that affective states exhibit degrees of independence from the concept of an object. She develops a new theory of the varieties of affect that explains their cognitive nature, their felt aspect, their special logic and the relationship between their objectless and object-directed forms. Armon-Jones concludes by suggesting that her arguments call into question certain assumptions about the rationality and moral status of affect and require a revision of the conception of the good in affect.